2014
DOI: 10.1155/2014/423708
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Success of Different Treatment Modalities for Management of Ectopic Pregnancy

Abstract: Aim. The purpose of this study was to investigate factors affecting the success of different treatment modalities for the management of ectopic pregnancy (EP). Methods. One hundred and ninety-seven patients with EP, were included in the study. Patients were treated with either intramuscular methotrexate (Mtx) or surgical treatment. Results. Mtx was applied in 97 (49.2%) patients. In 67 patients (69.1%), a single dose of Mtx and in 30 patients (30.9%) a multiple dose of Mtx was applied. Forty-seven (70.14%) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
(19 reference statements)
2
7
0
Order By: Relevance
“…In the present study, salpingectomy (laparoscopy or laparotomy) was performed in 74.3% cases which is similar to that found in a study carried out by Sümeyra et al (74.4%). 15 The rate of laparotomy (85%) was higher than the laparoscopy (15%) which is in consistent with Sümeyra et al 15 Obstetric hysterectomy was performed in 1 case of CSP following dilatation and evacuation due to uncontrolled and torrential haemorrhage. There have been many reasons for the increased rate of laparotomy in comparison to laparoscopy in the present research.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In the present study, salpingectomy (laparoscopy or laparotomy) was performed in 74.3% cases which is similar to that found in a study carried out by Sümeyra et al (74.4%). 15 The rate of laparotomy (85%) was higher than the laparoscopy (15%) which is in consistent with Sümeyra et al 15 Obstetric hysterectomy was performed in 1 case of CSP following dilatation and evacuation due to uncontrolled and torrential haemorrhage. There have been many reasons for the increased rate of laparotomy in comparison to laparoscopy in the present research.…”
Section: Discussionsupporting
confidence: 74%
“…Salpingo-oophorectomy was done in 2.8% cases (ruptured ovarian ectopic) in present study which correlated to Sümeyra et al (4.6%). 15 One case abdominal pregnancy (gestational age-26 weeks) was diagnosed per-operatively and was successfully managed by removal of fetus and placenta, which was implanted over posterior aspect of right sided broad ligament and was separated successfully. Management of placenta in abdominal pregnancy remains a controversial issue.…”
Section: Discussionmentioning
confidence: 99%
“…Using A'Hern's formula for Phase II one-stage designs [ 8 ], with 80% power and a 5% level of significance, 28 patients were required to enable us to assess whether the proportion of patients with a successful outcome to treatment was >70%. The reason we selected this figure is that methotrexate in the clinic appears to have a success rate of around 70% [ 9 , 10 ]. Our power calculation found if 24 or more patients have a successful outcome, we can reject the hypothesis that the true efficacy of combination gefitinib and methotrexate is ≤70%.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, Avcıuoglu et al in 2014 (30) reported no significant difference between single-dose (70.14% of treatment success) and double-dose (70%) regimen. They also depicted that in β-hCG levels<1000 IU/L, treatment success rises up to 86.11%, while in β-hCG levels>3000 IU/L treatment success was limited to 42.3%.…”
Section: Discussionmentioning
confidence: 96%